Pengembangan Buku Ajar pada Mata Kuliah Pendidikan IPS SD Jurusan PGSD Universitas Musamus - Hanip, Rival; Tembang, Yonarlianto; Nirtha, Eva (Musamus Journal of Primary Education, 2024)
Textbooks play a crucial role in the learning process. Therefore, it is important for the textbooks used to be contextual, taking into account the characteristics and environment of the students. This research aims to develop a supplementary book in the form of a contextual-based IPS SD textbook that is valid, engaging, practical, and effective. Data is collected through questionnaires, tests, and documentation. The results of data analysis indicate that the developed book meets the criteria of being valid, engaging, practical, and effective in learning. Thus, the textbook can be utilized as a better learning tool, supporting the success of the teaching and learning process in the classroom.